Efficacy of N-acetylcysteine in Preventing Acute Kidney Injury and Major Adverse Cardiac Events After Cardiac Surgery: A Meta-Analysis and Trial Sequential Analysis - Zhao, Jingtao; Li, Maowei; Tan, Chen (Frontiers in Medicine, 2022)
Background: The effect of N-acetylcysteine (NAC), an antioxidant, on preventing acute kidney injury (AKI) and major adverse cardiac events (MACE) remains controversial. Therefore, we conducted this meta-analysis and trial sequential analysis to evaluate its efficacy on the cardiac surgery related adverse events.Methods: PubMed, Embase and Cochrane Library were searched for relevant studies from inception to June 2021. We selected randomized controlled trials comparing NAC with controls in patients undergoing cardiac surgery.Results: Twenty-five studies including 2444 patients met the inclusion criteria. The pooled results showed that there was no significant difference in the incidence of AKI between the NAC and controlled groups (relative risk (RR) = 0.91, 95% confidence interval (CI) = 0.77, 1.08, P = 0.28), but the trial sequential analysis (TSA) could not confirm this result. No difference was observed in the need for renal replacement therapy (RRT), all-cause mortality, length of stay in intensive care unit (ICU) and length of stay in hospital (RR = 1.06, 95% CI = 0.58, 1.95, P = 0.85; RR = 0.72, 95% CI = 0.41, 1.25, P = 0.24; mean difference (MD) = -0.07, 95% CI = -0.28, 0.14, P = 0.54; MD = -0.16, 95% CI = -0.59, 0.27, P = 0.45; respectively). The occurrence of MACE, including arrhythmia, cardiac insufficiency and acute myocardial infarction is also similar in the NAC and the controlled groups.Conclusion: NAC did not reduce the risk of AKI and MACE in patients undergoing cardiac surgery. Larger sample size randomized controlled trials are needed to further investigate these postoperative complication outcomes.